PROFIL PENGGUNA JASA WARNET DI PEKANBARU - Putri, Yurika Andini; Razif, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study describes the Service Internet Cafe User Profile in Pekanbaru. Motivated by the phenomenon of the rapid development of internet cafe in Pekanbaru, both of which only have one function, such as Game Center, as well as the proper functioning of all the sites to be visited by the user. In Pekabaru registered 119 figuring that spread across the city, including in the area of Jalan taka Hrapan Kingdom. In this area, there are about 20 figuring that operated 24 hours.The shape of this research is qualitative, which describes the overall profile of the Internet service users. Accidental sampling is a technique of data collection to be 5 levels of education as a population. Of all the population is, in each take 2 people from each grade.From the obtained results of this study indicate that male users are more and more often to use the cafe as a place to relieve their boredom compared with female users. Age and education levels are also strongly associated with what sites they use or visit when surfing. Online Games Couter Stike, social, media, Search Engine, Wiki, Media Sharing, News and Information Portal, Blogs, Forums and Online Store are 9 sites most preferred Internet service users.Keywords: Service Internet Cafe , User Profile